2023
DOI: 10.4236/ojepi.2023.132009
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices of the Populations of Dapaong and Its Surroundings in Togo on Sodium/Salt and Potassium Intakes

Abstract: Background: Food plays an important role in human health. A healthy diet contributes to the improvement of the health of populations. A diet high in sodium/salt and low in potassium has been shown to contribute to cardiovascular disease. The objective of this study was to assess the knowledge, attitudes and practices (KAP) of the inhabitants of Dapaong and its surroundings on dietary intakes of sodium/salt and potassium. Methods: This was a cross-sectional study conducted from 1 November to 15 December 2022 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Many factors, including biological and behavioural ones, affect a person's risk for hypertension. The three key lifestyle elements that can be adjusted are smoking, eating, and exercise [10]. Restricting salt may lower blood pressure in all age groups and in both men and women.…”
Section: Original Articlementioning
confidence: 99%
“…Many factors, including biological and behavioural ones, affect a person's risk for hypertension. The three key lifestyle elements that can be adjusted are smoking, eating, and exercise [10]. Restricting salt may lower blood pressure in all age groups and in both men and women.…”
Section: Original Articlementioning
confidence: 99%
“…All in all, a good level of knowledge about the consumption of sodium versus potassium foods predisposes to a healthy diet. A study in the same locality found that people had poor knowledge of health-promoting behaviours regarding dietary intakes of sodium and potassium [28]. Thus, regardless of sociodemographic factors, it is important to have optimal knowledge of dietary sodium and potassium intakes, hence the importance of promoting a diet based on a healthy lifestyle and favourable to the fight against cardiovascular disease [29].…”
Section: Factors Associated With High Consumption Of Green Leafy Vege...mentioning
confidence: 99%